#### Answer

False

#### Work Step by Step

Step 1:
-3(x + 5y) = -3(14)
-3x - 15y = -42
Step 2:
3x - 2y = -9
+
-3x - 15y = = -42
=
-17y = -51
Result:
The y's are not eliminated; the x's are eliminated.

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

False

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.